Yield Performance and Economic Analysis of Pigeon pea (Cajnus cajan) Through Front Line Demonstration under Rainfed Condition of Tarai Region of Uttar Pradesh - Singh, Narendra (International Journal of Bio-resource and Stress Management, 2020)
Seventy five demonstrations in the farmers’ fields were conducted on Pigeon pea during 2009-10 to 2013-14 in 5 adopted locations (villages) namely Khajurinidhi, Sukulan purwa, Jai Prabha gram, Chhiras and Peoli of Gonda district, Uttar Pradesh state, India under Tarai agro-climatic zone. The critical inputs were prioritized according to gap analysis on existing production technologies through Participatory Rural Appraisal (PRA), farmer’s interaction and feedback. In demonstration plot, latest recommended package of practices were adopted as good quality seed, weed management, integrated nutrient management, timely sowing on ridges were made to reduce crop mortality due to water logging and management of pests at proper time. The 5-years data revealed that an average higher yield of demonstration field was obtained 1.831 t ha-1 over local check (1.002 t ha-1) with additional yield of 0.829 t ha-1 due to timely technological support in demonstration fields. Similarly, net average economic return of demonstration plot was found Rs. 41652 ha-1 over local check (Rs. 20410 ha-1) with additional return of Rs. 21242 ha-1. The average technological gap, extension gap, technological index and increased B:C ratio were found 0.969 t ha-1, 0.829 t ha-1, 34.61% and 0.95, respectively. Data revealed significantly impact of latest technologies in compare to traditional Pigeon pea cultivation under demonstrated farmer’s fields during the years.